Characterization of bioactive compounds and antibacterial study of pitaya peel extract extracted through microwave assisted extraction method - Muhammad Azlan, Nazeri (2018)
Pitaya peel is a potential form of fruit waste, especially within the food industry, mainly because its juice extract can be applied as natural coloring. It also contains beneficial bioactive compounds with commercial value, along with antioxidant and antibacterial properties that have a good impact upon the human health. With such potentials of the pitaya peel, unfortunately, it is discarded without treatment in food processing industries by ignoring the side effects it has towards the environment. Only a handful of studies have analyzed the bioactive compounds of pitaya peel extract via green method, which applies water and microwave assisted extraction (MAE) as solvent and tool for the respective extraction processes. Thus, the key objective of the current study is determining the best conditions of MAE in attaining the maximum total phenolic content (TPC) value. These conditions have been applied in extracting bioactive compounds from the pitaya peel, specifically mineral and phenolic compounds. Then, the chemical contents are characterized before the antibacterial activity of the extracts can be analysed and studied. Freeze dryer technique was used to remove the water content in the pitaya peel before extraction so that the pitaya peel can be stored for a longer period prior to analysis. The effects of MAE parameters, such as power, temperature, sample weight, and time, were determined. Inductively coupled plasma-optical emission spectrometry (ICP-OES) and ultra-high performance liquid chromatography coupled mass spectrometer (UHPLC-ESI-QTRAP-MSMS) had been utilized to analyze the mineral content and the type of phenolic compounds found in pitaya peel extract. The antibacterial analysis of pitaya peel extract was performed against Gram-positive, Staphylococcus aureus (S. aureus) ATCC 6538, and Gram-negative, Escherichia coli (E. coli) ATCC 8739, to determine the modification that took place at the inhibition zone. Time-kill kinetics assay was applied to monitor the bacterial growth curve. Additionally, two software programs were employed; SPSS and CCLASS, in order to determine the best condition of MAE based on significant variance between TPC mean value and validated data of mineral content from pitaya peel extract, respectively. The microscopic structural changes of pitaya peel before and after extraction on MAE had been observed as well. The outcomes revealed that the maximum TPC values were retrievable at 400 W power, 45 °C temperature, and 20 min contact time to extract 1.2 g of pitaya peel in 50 mL of water at 5.808, 5.800, 5.723, and 5.708 mg GAE/g dried peel, respectively. These best condition parameters were verified via SPSS with Bonferroni post hoc. The TPC values recorded from the liquid extract was measured in mg GAE/g, while Inhibitory Concentration unit (IC50) was determined from the extract by applying the best condition parameters of MAE and 2,2, diphenyl-1-picrylhydrazil (DPPH) reagents as synthetic free radicals. The IC50 value recorded in this study was 0.52 mL/mL. Furthermore, 12 out of 24 elements were identified, including Ba, Ca, Cu, Cd, Fe, K, Mg, Mn, Na, Ni, Sr, and Zn, whereas 13 phenolic compounds significantly matched the mass spectral database. Nevertheless, the pitaya peel extract had no inhibition zone area, but displayed a small effect on the time-kill kinetics analysis. In short, pitaya peel extract seems to be enriched with valuable mineral contents and phenolic compounds, along with low antibacterial properties. The scanning electron microscopy (SEM) demonstrated that cell wall disruption of pitaya peel caused by microwave radiation from MAE appeared to be the main reason for rapid extraction of bioactive compounds. As a conclusion, the extraction bioactive compounds from pitaya peel exhibited potential application that could substantially reduce wastes produced by the food processing industry.